Preparation and electrical properties of ZnO‐Bi2O3‐based multilayer varistors with base metal nickel inner electrodes. Issue 7 (10th April 2017) - Chen, Tao; Zu, Hao; Gao, Chao; Ke, Chunfeng; Zhou, Dongxiang; Hu, Yunxinag; Zheng, Zhiping; Fu, Qiuyun
Abstract: In this study, ZnO‐Bi2 O3 ‐based multilayer varistors (MLVs) cofired with nickel (Ni) inner electrodes were prepared by tape‐casting method. Samples were sintered in pure nitrogen (N2 ) to keep Ni from being oxidized, and then reoxidized in air to obtain the nonlinear properties (reduction‐reoxidation method). The EDAX results showed that Ni inner electrodes are stable and have no evident migration into ZnO‐Bi2 O3 ‐based ceramics when sintered in N2 . The influence of reoxidation temperature on microstructures and nonlinear properties of samples were studied. Samples reoxidized at the temperatures lower than 650°C showed poor nonlinear properties. After reoxidized in air at 700°C for 2 hours, samples exhibited nonlinear properties of V 1 mA =16.3 V, α=26.5, I L =0.68 μA. At the reoxidation temperature higher than 750°C, the oxidation of Ni inner electrodes deteriorated the nonlinear properties of samples. It demonstrated that ZnO‐Bi2 O3 ‐based MLVs with base metal Ni inner electrodes proposed in this work are suitable for reduction‐reoxidation method. The replacement of noble metals Pt or Ag/Pd alloys by base metal Ni is expected to lower the cost of ZnO‐Bi2 O3 ‐based MLVs.